Childhood psychological distress and youth unemployment: Evidence from two British cohort studies. (January 2015) - Egan, Mark; Daly, Michael; Delaney, Liam
Abstract: The effect of childhood mental health on later unemployment has not yet been established. In this article we assess whether childhood psychological distress places young people at high risk of subsequent unemployment and whether the presence of economic recession strengthens this relationship. This study was based on 19, 217 individuals drawn from two nationally-representative British prospective cohort studies; the Longitudinal Study of Young People in England (LSYPE) and the National Child Development Study (NCDS). Both cohorts contain rich contemporaneous information detailing the participants' early life socioeconomic background, household characteristics, and physical health. In adjusted analyses in the LSYPE sample ( N = 10, 232) those who reported high levels of distress at age 14 were 2 percentage points more likely than those with low distress to be unemployed between ages 16 and 21. In adjusted analyses of the NCDS sample ( N = 8985) children rated as having high distress levels by their teachers at age 7 and 11 were 3 percentage points more likely than those with low distress to be unemployed between ages 16 and 23. Our examination of the 1980 UK recession in the NCDS cohort found the difference in average unemployment level between those with high versus low distress rose from 2.6 pct points in the pre-recession period to 3.9 points in the post-recession period. These findings point to a previously neglected contribution of childhood mental health to youth unemployment, which may be particularly pronounced during times of economic recession. Our findings also suggest a further economic benefit to enhancing the provision of mental health services early in life. Highlights: This study examines the association between childhood distress and youth unemployment. Two prospective studies with over one million observations on 19, 217 individuals. Children with high distress were 2.5 pp more likely to become unemployed across both studies. Distress is more strongly linked with unemployment during economic recession. Findings suggest economic benefits to improving mental health services early in life.